2020
DOI: 10.3390/brainsci10120998
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Filtered Emotional Faces Dominate during Binocular Rivalry

Abstract: The present investigation explores the role of bottom-up and top-down factors in the recognition of emotional facial expressions during binocular rivalry. We manipulated spatial frequencies (SF) and emotive features and asked subjects to indicate whether the emotional or the neutral expression was dominant during binocular rivalry. Controlling the bottom-up saliency with a computational model, physically comparable happy and fearful faces were presented dichoptically with neutral faces. The results showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 71 publications
2
5
0
Order By: Relevance
“…3A). The further pairwise comparison suggested that the emotional dominance on the neutral-happy rivalry condition was signi cantly stronger than that on the neutral-fear rivalry condition (0.039 ± 0.167 vs. − 0.028 ± 0.117, p = 0.001) and on the neutral-sad rivalry condition (0.039 ± 0.167 vs. − 0.007 ± 0.136, p = 0.021), in consistent with previous reports demonstrating a more pronounced emotion bias for the happy expression in binocular rivalry (e.g., [12,21]). There is no a signi cant difference on the emotional dominance between the neutral-fear rivalry condition and the neutral-sad rivalry condition (− 0.028 ± 0.117 vs. − 0.007 ± 0.136, p = 0.275).…”
Section: Emotional Dominancesupporting
confidence: 91%
See 2 more Smart Citations
“…3A). The further pairwise comparison suggested that the emotional dominance on the neutral-happy rivalry condition was signi cantly stronger than that on the neutral-fear rivalry condition (0.039 ± 0.167 vs. − 0.028 ± 0.117, p = 0.001) and on the neutral-sad rivalry condition (0.039 ± 0.167 vs. − 0.007 ± 0.136, p = 0.021), in consistent with previous reports demonstrating a more pronounced emotion bias for the happy expression in binocular rivalry (e.g., [12,21]). There is no a signi cant difference on the emotional dominance between the neutral-fear rivalry condition and the neutral-sad rivalry condition (− 0.028 ± 0.117 vs. − 0.007 ± 0.136, p = 0.275).…”
Section: Emotional Dominancesupporting
confidence: 91%
“…The alternations continue over time. Many previous studies have demonstrated that such temporal dynamics of binocular rivalry is affected not only by low-level physical properties of rivaling stimuli such as contrast (e.g., [16,17]) and spatial frequency (e.g., [18,19]) but also by high-level properties of rivaling stimuli such as emotionality (e.g., [20,21]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The switches would continue over time. Many previous studies have demonstrated that such temporal dynamics of binocular rivalry are affected not only by low‐level visual properties of rivaling stimuli, such as contrast (e.g., Hollins, 1980; Qiu et al, 2020) and spatial frequency (e.g., Piazza & Silver, 2017; Wade, 1975), but also by high‐level properties of rivaling stimuli, such as emotionality (e.g., Coren & Russell, 1992; Turano et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Faces convey peculiar and biologically relevant information, providing a huge variety of socially relevant signals [1][2][3][4][5][6]. Given the fundamental information conveyed by faces (i.e., age, gender, identity, and mood), face recognition is essential for human social functioning throughout the entire lifespan.…”
Section: Introductionmentioning
confidence: 99%